Oxygen radical antioxidant capacity (ORAC) and antibacterial properties of Melicope glabra bark extracts and isolated compounds - Quek, Alexandra; Mohd Zaini, Hafizah; Kassim, Nur Kartinee; Sulaiman, Fadzil; Rukayadi, Yaya; Ismail, Amin; Zainal Abidin, Zamirah; Awang, Khalijah (Public Library of Science, 2021)
Melicope glabra (Blume) T. G. Hartley from the Rutaceae family is one of the richest sources of plant secondary metabolites, including coumarins and flavanoids. This study investigates the free radical scavenging and antibacterial activities of M. glabra and its isolated compounds. M. glabra ethyl acetate and methanol extracts were prepared using the cold maceration technique. The isolation of compounds was performed with column chromatography. The free radical scavenging activity of the extracts and isolated compounds were evaluated based on their oxygen radical absorbance capacity (ORAC) activities. The extracts and compounds were also subjected to antibacterial evaluation using bio-autographic and minimal inhibitory concentration (MIC) techniques against two oral pathogens, Enterococcus faecalis and Streptococcus mutans. Isolation of phytoconstituents from ethyl acetate extract successfully yielded quercetin 3, 5, 3’-trimethyl ether (1) and kumatakenin (2), while the isolation of the methanol extract resulted in scoparone (3), 6, 7, 8-trimethoxycoumarin (4), marmesin (5), glabranin (6), umbelliferone (7), scopoletin (8), and sesamin (9). The study is the first to isolate compound (1) from Rutaceae plants, and also the first to report the isolation of compounds (2–5) from M. glabra. The ORAC evaluation showed that the methanol extract is stronger than the ethyl acetate extract, while umbelliferone (7) exhibited the highest ORAC value of 24 965 μmolTE/g followed by glabranin (6), sesamin (9) and scopoletin (8). Ethyl acetate extract showed stronger antibacterial activity towards E. faecalis and S. mutans than the methanol extract with MIC values of 4166.7 ± 1443.4 μg/ml and 8303.3 ± 360.8 μg/ml respectively. Ethyl acetate extract inhibited E. faecalis growth, as shown by the lowest optical density value of 0.046 at a concentration of 5.0 mg/mL with a percentage inhibition of 95%. Among the isolated compounds tested, umbelliferone (7) and sesamin (9) exhibited promising antibacterial activity against S. mutans with both exhibiting MIC values of 208.3 ± 90.6 μg/ml. Findings from this study suggests M. glabra as a natural source of potent antioxidant and antibacterial agents.